Lie. árškus ir jo giminaičiai - Karaliūnas, Simas (Baltistica, 1994)
LITH. árškus „CLEAR, SERENE” AND ITS COGNATES Lith. árškus most likely goes back to the stem *arg̑u- < *h2erg̑u- found in OInd. árju-na- „shining, white”, Gr. ά̉ργυ-φος „id.” to which -šk- was added on the analogy with the synonyms áiškus „clear“, ráiškus „clear, distinct”. The initial a- was lengthened both in Baltic and Tocharian (A ārki, В ārkwi “white") apparently through the effect of a preceding laryngeal. Because of synesthesia Lith. aržùs „strong, violent, hot-tempered; lustful, lewd” < *„quick, rapid, fast” came into being. Coexistence of „shining, radiant, white” and „quick, rapid, fast’ is widely attested in Old Indian and Greek. The river and lake names Érzvėtas, Erzvėtaĩ, Erzvėtà are ambiguous in regard to the root vocalism. Their *Eržu̯-, dialectically *Erzu̯- reflect either *áržu- < *h2erg̑u- or *éržu- < *h2ērg̑u- (with the lengthened grade of the root vowel). The river name Eržvilkaĩ < *Erži-vilkaĩ, metaphorically „quick wolves” may be semantically and syntagmatically compared with OInd. Rjí-śvan-, Gr. κύνες α̉ργοί „fast running dogs”. IE. *h2r̥g̑i- > OInd. r̥ji- seems to have been transformed into *erg̑i- > *er̃ži- (with full grade vowel) in Baltic, though.